2015
DOI: 10.1097/shk.0000000000000389
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic Acetylcholine Receptor is a Novel Mediator of Sinomenine Anti-Inflammation Effect in Macrophages Stimulated by Lipopolysaccharide

Abstract: Sinomenine (SIN), an alkaloid derived from the plant Sinomenium acutum, has anti-inflammatory and analgesic effects and has been used for rheumatoid arthritis treatment in China. This study aims to verify the hypothesis that SIN acts on α7 nicotinic acetylcholine receptor (α7nAChR) to inhibit the activation of macrophages stimulated by lipopolysaccharide. The prototypical α7nAChR antagonist α-bungarotoxin and mecamylamine attenuated the effect of SIN on tumor necrosis factor-α and interleukin-6 in RAW264.7 mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…This is termed cholinergic anti-inflammatory pathway678. We have shown that anisodamine (Ani) promotes the binding of α7nAChR to endogenous acetylcholine and blocks muscarinic receptors910.…”
mentioning
confidence: 99%
“…This is termed cholinergic anti-inflammatory pathway678. We have shown that anisodamine (Ani) promotes the binding of α7nAChR to endogenous acetylcholine and blocks muscarinic receptors910.…”
mentioning
confidence: 99%
“…Phytoconstituents have several limitations such as non‐uniformity in dose and poor bioavailability, higher metabolism and larger biodistribution characteristics. There are limited data available on polyphenolic concentration in human tissues . In another way, the polyphenols have only 2–20% oral bioavailability.…”
Section: Challenges With Herbal Pharmacotherapymentioning
confidence: 99%
“…In another way, the polyphenols have only 2–20% oral bioavailability. Majority of the polyphenols are instantly metabolized via methylation, sulphation, glucuronidation and eliminated by liver, which results into poor bioavailability …”
Section: Challenges With Herbal Pharmacotherapymentioning
confidence: 99%
See 2 more Smart Citations